SISTEM KODE DALAM CERPEN DINI BERIBU ULAR KARYA FARIZAL SIKUMBANG: KAJIAN SEMIOTIKA ROLAND BARTES - Pangestu, Vivi Riana; Zakia, Nindi; Maharany, Amalia Putri (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2024)
The short story Dini Beribu Ular by Farizal Sikumbang has an unique code or meaning system to analyze. The purpose of this study is to describe the five code systems contained in the short story Dini Beribu Ular by Farizal Sikumbang. This study uses a qualitative descriptive method in examining the five code systems proposed by Roland Barthes. The results of the study found five code systems with a total of 7 data in the short story Dini Beribu Ular by Farizal Sikumbang consisting of 3 data, namely the action/action/proairetic code (proairetik code), 1 data puzzle/hermeneutic code (hermeneutical code), 1 data cultural code (cultural code), 1 data connotative code (connotative code), and 1 data symbolic code (symbolic field).